Mass Integration for Rigorous Process Modelling: A Sequential Approach for Direct Recycling - Marchione, Filippo; Hungerbuehler, Konrad; Papadokonstantakis, Stavros (Frontiers in Chemical Engineering, 2021)
Mass integration has been used for reducing the amount of process waste and environmental impact. Despite its long history, new challenges constantly arise with the use of process simulation tools offering platforms for rigorous process models. Therefore, the typical mass integration framework requires modifications to accurately account for the process performance. In this work, a novel sequential methodology is presented to realize a recycle network with rigorous process models. Initially, under the hypothesis of constant compositions of the process sources, an optimal ranking of the process sinks is determined. The optimal recycling network thus obtained is then used for a sequential methodology considering rigorous process models. The violations of process constraints are handled at each sequential step through the concept of “tightening constant”. The application of the sequential methodology to two case studies proves its ability to provide good approximations of the global optima with low computational effort.